Analisis Potensi Risiko Kesehatan Dan Keselamatan Kerja (K3) Dengan Metode Hirarc Pada Area Nondestructive Testing (NDT) Di Workshop Gmf Aeroasia - Zaidan Irfan A.F.R (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Occupational Safety and Health (OSH) is a crucial aspect of the aviation industry, which is characterized by a high level of occupational risk and complex operational activities. One of the high-risk work areas at PT Garuda Maintenance Facility (GMF) AeroAsia is the Non-Destructive Testing (NDT) division, where employees are exposed to hazardous chemicals, radiation, and high-voltage equipment. This study aims to analyze occupational safety and health risks in the NDT area using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. The research employed a descriptive qualitative approach through field observations, interviews with NDT technicians and OSH personnel, and a review of the company's existing Hazard Identification and Risk Assessment (HIRA) documents. The findings indicate that HIRA procedures have been implemented; however, several shortcomings remain, including outdated hazard identification records, limited technicians' understanding of HIRA documentation, and insufficient worker involvement in the risk assessment process. In addition, risk control measures are still primarily focused on the use of personal protective equipment (PPE) without fully implementing the hierarchy of controls. This study recommends strengthening HIRA-based OSH training, conducting regular updates of risk assessment documents, and increasing worker participation in hazard identification and risk assessment activities. The findings are expected to contribute to the improvement of the occupational safety and health management system within the Non-Destructive Testing (NDT) work environment at PT Garuda Maintenance Facility (GMF) AeroAsia.